Parkinson's Disease Risk and Alcohol Intake: A Systematic Review and Dose-Response Meta-Analysis of Prospective Studies - Shao, Chuan; Wang, Xiaoya; Wang, Pan; Tang, Hui; He, Jiaquan; Wu, Nan (Frontiers in Nutrition, 2021)
Background: The association between Parkinson's disease (PD) risk and alcohol intake is a controversial topic. Objectives: To systematically assess the association between PD risk and alcohol intake. Methods: PubMed and Embase databases were searched for eligible studies with prospective design on PD risk and alcohol intake. A meta-analysis with a random-effects model and dose-response analysis was performed. Relative risk ratios (RRs) with 95% CIs were calculated. Results: Eleven prospective studies were included. Overall, a higher intake of alcohol was inversely associated with PD risk (RR: 0.81, 95% CI: 0.70–0.95, I2 = 73.7%). Significant differences existed between the specific types of alcoholic beverages and geographic area. Specifically, a significant association existed for beer (RR: 0.78, 95% CI: 0.65–0.94, I2 = 0.0%) and studies conducted in Asia (RR: 0.66, 95% CI: 0.55–0.80, I2 = 37.3%). Dose-response analysis indicated a nonlinear relationship between PD risk and alcohol exposure. No evidence for publication bias was detected. Conclusions: In summary, our meta-analysis suggests that alcohol consumption was associated with a decreased risk of PD, with a nearly U-shaped association. Future studies are warranted to clarify the question of a specific type of alcoholic beverage-dependent association, geographic area effect, and possible threshold effects regarding both the adverse and beneficial effects of alcohol.